The Battle for God - Karen Amstrong (Alfred A. Knopf, a division of Random House, I, 2000)
About 40 years ago popular opinion assumed that religion would become a weaker force and people would certainly become less zealous as the world became more modern and morals more relaxed. But the opposite has proven true, according to theologian and author Karen Armstrong, who documents how fundamentalism has taken root and grown in many of the world's major religions, such as Christianity, Islam, and Judaism. Even Buddhism, Sikhism, Hinduism, and Confucianism have developed fundamentalist factions. Reacting to a technologically driven world with liberal Western values, fundamentalists have not only increased in numbers, they have become more desperate, claims Armstrong, who points to the Oklahoma City bombing, violent anti-abortion crusades, and the assassination of President Yitzak Rabin as evidence of dangerous extremes. Yet she also acknowledges the irony of how fundamentalism and Western materialism seem to urge each other on to greater excesses. To "prevent an escalation of the conflict, we must try and understand the pain and perception of the other side," she pleads. With her gift for clear, engaging writing and her integrity as a thorough researcher, Armstrong delivers a powerful discussion of a globally heated issue. Part history lesson, part wake-up call, and mostly a plea for healing, Armstrong's writing continues to offer a religious mirror and a cultural vision.